Strong [compact disc] - Hubbard, Tyler Reed, 1987- (EMI Nashville, 2024)
With more than one billion streams as a solo artist and two back-to-back number one singles, Tyler Hubbard's sophomore solo album features 13 brand-new songs, including Back Then Right Now; Turn; and Wish You Would.